Vibrational response of a rectangular duct of finite length excited by a turbulent internal flow. (26th May 2018) - David, Antoine; Hugues, Florian; Dauchez, Nicolas; Perrey-Debain, Emmanuel
Abstract: Gas transport ductwork in industrial plants or air conditioning networks can be subject to vibrations induced by the internal flow. Most studies in this matter have been carried out on circular ducts. This paper focuses specifically on the vibratory response of a rectangular duct of finite length excited by an internal turbulent flow. A semi-analytical model taking into account the modal response of the structure due to both aerodynamic and acoustic contributions is derived. The aerodynamic component of the excitation is applied on the basis of Corcos model where the power spectral density of the wall pressure is determined experimentally. The acoustic component is based on the propagating modes in the duct where the acoustic modal contribution are extracted via cross-spectral densities. The vibrational response is given for a 0.2 × 0.1 × 0.5 m 3 duct made of 3 mm steel plates excited by 20 m/s or 30 m/s flows. Comparisons between experimental results and numerical predictions show a good agreement. The competition between acoustic and aerodynamic components is highlighted.